المعالجة القلبية للاضطرابات النفسية من منظور قرآني والعلاج النفسي المعاصر: دراسة مقارنة: The Heart-Based Healing of Psychological Disorders from the Qur'anic Perspective and Contemporary Psychotherapy: A Comparative Study - Dr. Hafiz Ahmad Hammad; Al-Makawi, Dr. Ahmad Nabih (Al Basirah, 2025)
Psychological disorders are a significant issue in modern society, and their treatment requires a multifaceted approach. This article explores heart-based healing for psychological disorders from both a Qur'anic perspective and contemporary psychological treatments. The Qur'an emphasizes the importance of a pure heart for mental and spiritual well-being. Key verses stress the necessity of a pure heart. Previously various researchers have examined heart related diseases and illness in the light of Quran and Sunnah, their core focus is mostly on purification of heart spiritually not to heal the psychological disorders. For example Dr. Muhammad Hassan Yaqub has written on "Diseases of the heard in the light of the Holy Quran". Dr Abdul Hameed Al-Qudah's work "Psychological tranquility in the light of The Quran", that focuses on how to achieve tranquility by Quran. However Quranic perception of healing a psychological disorder and reviewing the present day psychotherapies is still unexamined. This study fills this gap to review the psychological disorders and contemporary psychotherapy in Islamic perspective. Islamic scholars state that a sound heart is free from polytheism and sins, leading to psychological peace. Contemporary psychology, on the other hand, focuses on therapies like cognitive-behavioral therapy and relaxation techniques to address mental health. Experts highlighted that emotional and psychological balance is crucial for treatment. This study suggests that integrating Qur'anic wisdom with modern psychological practices offers a holistic approach, combining spiritual purification and psychological insight to treat psychological disorders effectively.